Calculative Principles of Required Pressure for Decolmatation of Pre-Filter Zone of Water Intake Well - V. V. Ivashechkin (Наука и техника)
The paper presents main calculative principles of the required pressure which is initiated in the cavity of colmatated rod and frame filter proceeding from the provision of its regeneration. Colmatation is schematized as an annular zone including gravel filter pack grouted by colmatage matter and water intake surface which being bonded to one another jointly operate under load. Expressions have been deduced with the purpose to determine ultimate (limiting) pressure values for 3 stages of filter operation: 1. formation of non-through cracks in the filter pack; 2. formation of through cracks; 3. destruction of water intake surface of the filter.The paper considers a numerical example of calculation pertaining to determination of operational interval of pressures which are required for treatment of rod and frame filter with pre-set strength of the clogged gravel filter pack. It has been ascertained that the required pressure value is determined to a great extent by tensile strength of the water intake surface.